Effects of obesity on severity of menopausal symptoms in urban and rural women - Sudha Bakthavathsalam Sreenivas; Pranav Balaji Kashyap (Journal of Mid-Life Health, 2022)
Background: According to the WHO, obesity is an epidemic and is quantified by obesity indices. Menopause is a crucial period with a tendency toward weight gain and has profound implications on the morbidity and mortality of women. This study provides a greater insight into the aggravating adverse effects of obesity on the lifestyles of urban and rural women during their menopausal phase. Hence, this cross-sectional study aims at analyzing the effects of obesity indices on the severity of menopausal symptoms in urban and rural women. Objectives: 1. To compare the obesity indices in rural and urban women and to study the severity of menopausal symptoms in them. 2. To assess the influence of the area and body mass index (BMI) on menopausal symptoms. Materials and Methods: This cross-sectional study comprised 120 women, of which 60 healthy women volunteers between the age group of 40 and 55 years from the urban area and 60 age-matched healthy women volunteers from the rural area were recruited. The sample size was calculated based on stratified random sampling. After obtaining informed consent anthropometric measurements were recorded and the Menopausal Rating Scale was used for assessing the severity of menopausal symptoms. Results: A positive correlation was observed between the severity of menopausal symptoms and BMI as well as waist circumference in urban women. The problems related to menopausal symptoms were milder in rural women. Conclusions: Our study concludes that obesity worsens the severity of several menopausal symptoms which is greater among obese urban women owing to the urban lifestyle and increased stress levels.